The Applications of Carbon Nanotubes in the Diagnosis and Treatment of Lung Cancer: A Critical Review - Sheikhpour M (Dove Medical Press, 2020)
Mojgan Sheikhpour,1,2 Maryam Naghinejad,1,2 Alibakhsh Kasaeian,3 Armaghan Lohrasbi,1,2 Seyed Sadegh Shahraeini,1,2 Shahab Zomorodbakhsh4 1Department of Mycobacteriology and Pulmonary Research, Pasteur Institute of Iran, Tehran, Iran; 2Microbiology Research Center (MRC), Pasteur Institute of Iran, Tehran, Iran; 3Faculty of New Sciences and Technologies, University of Tehran, Tehran, Iran; 4Department of Chemistry, Mahshahr Branch, Islamic Azad University, Mahshahr, IranCorrespondence: Mojgan Sheikhpour Tel +989122969712Email m_sheikhpour@pasteur.ac.irAbstract: The importance of timely diagnosis and the complete treatment of lung cancer for many people with this deadly disease daily increases due to its high mortality. Diagnosis and treatment with helping the nanoparticles are useful, although they have reasonable harms. This article points out that the side effects of using carbon nanotube (CNT) in this disease treatment process such as inflammation, fibrosis, and carcinogenesis are very problematic. Toxicity can reduce to some extent using the techniques such as functionalizing to proper dimensions as a longer length, more width, and greater curvature. The targeted CNT sensors can be connected to various modified vapors. In this regard, with helping this method, screening makes non-invasive diagnosis possible. Researchers have also found that nanoparticles such as CNTs could be used as carriers to direct drug delivery, especially with chemotherapy drugs. Most of these carriers were multi-wall carbon nanotubes (MWCNT) used for cancerous cell targeting. The results of laboratory and animal researches in the field of diagnosis and treatment became very desirable and hopeful. The collection of researches summarized has highlighted the requirement for a detailed assessment which includes CNT dose, duration, method of induction, etc., to achieve the most controlled conditions for animal and human studies. In the discussion section, 4 contradictory issues are discussed which are invited researchers to do more research to get clearer results.Keywords: carbon nanotubes, toxicity, lung cancer detection, lung cancer treatment, drug delivery